Piano Music of Robert Schumann, Series II - SCHUMANN, Robert (Dover Publicatons, Inc., 1972)
Di dalam buku ini terdapat 10 lagu: Humoreske, Op.20; Novelletten, Op. 21; Sonate No.2, Op. 22; Nachtstucke, Op. 23; Nachtstucke, Op. 23; Faschingsschhwank aus Wien, Op, 26; 43 Clavierstucke fur de Jugend, Op. 68; 4 furgen, Op.72; Waldscenen, Op.82; Bunte Blatter, Op. 99; 3 Calvier-sonaten fur die Jugend,Op.118